Outsourcing, performance, and the role of e-commerce: A dynamic perspective - Kotabe, Masaaki; Mol, Michael J.; Murray, Janet Y. (Industrial marketing management, 2008)
In a highly competitive global environment, many manufacturers respond by setting up outsourcing relations for components and finished products with lower-cost producers on a contractual OEM (original equipment manufacture) basis. In the last decade, we have witnessed a spectacular growth in outsourcing activities led primarily by U.S. and Japanese companies, although their approaches to outsourcing strategy and supplier relations are different. However, outsourcing strategy is not without drawbacks. We offer a dynamic perspective of outsourcing strategy and its performance implications, in which we argue that there is an optimal degree of outsourcing. The outsourcing-performance relationship takes on an inverted-U shape, implying that as firms deviate further from their optimal degree of outsourcing, by either insourcing or outsourcing too much, their performance will suffer disproportionately. We then discuss how e-commerce affects where the optimal point of any particular firm is located, hence explicitly linking developments in e-commerce to changing outsourcing levels. We provide implications for the practice and study of outsourcing and e-commerce.